Does profession or experience affect a practitioner's perception when assigning potential harm avoided by pharmacists interventions. Issue 6 (9th May 2013) - Hussain, A; Isaac, R; Rodrigues, D
Abstract : Aim: The aims of the study were to assess the differences in rating of potential harm avoided by a pharmacist's intervention using a multidisciplinary team and whether the experience of a healthcare professional affects how an intervention is rated. Method: A random sample of 30 pharmacist interventions made on a neurosurgical ward were tabulated and sent to a multidisciplinary panel for review and grading using the National Reporting and Learning System risk scoring, one being negligible harm and five being catastrophic. 1 Each intervention was subjected to the Medication Error Reporting and Prevention Index for categorising actual medication errors. 2 The panel consisted of a consultant neurosurgeon, neurosurgical registrar, specialist nurse, senior pharmacist and junior pharmacist. Data included demographic and clinical details of the patient and the intervention made by the ward pharmacist. Each individual was asked to score each of the 30 interventions in terms of potential harm had the pharmacist not intervened. Results: The mode for this data set was 2, the median was 3 and the range was 4. The neurosurgical registrar rated the interventions with the highest average intervention score of 2.1. The neurosurgical consultant and the junior pharmacist both had an average intervention score of 2.06. The specialist nurse and the senior pharmacist had the lowest average score for the interventions which were 1.93 and 1.8 respectively. 21 of the 30 interventions were made prior to the administration of the prescribed medication. An example of a high scoring intervention is the failure to prescribe buccal midazolam for a child who suffers with seizures, severe enough to warrant a stay in our paediatric intensive care unit. The basic grade pharmacist and the neurosurgical consultant were the only two who categorised any of the interventions as catastrophic. The specialist nurse categorised four of the interventions at a category of moderate to catastrophic, whereas the senior pharmacist categorised three within this category. Nine (30%) of the interventions made involved the use of antibiotics. 33% of these interventions related to antibiotic drug omissions and 33% related to under dosing the patient with antibiotics. These under doses reported were due to the Trust switching from the use of cefuroxime to cefotaxime (in the neurosurgical ward) as a first line antibiotic which was being used at a dose of 30 mg/kg instead of the standard 50 mg/kg. Conclusions: The results show that professionals with similar experiences score interventions similarly such as the specialist nurse and senior pharmacist (both sit on the Trust Medicines Safety Committee) or the neurosurgical registrar and consultant. Future study will include a larger cohort from the medical, pharmacy and nursing team.